Resurrection of an East African house bat species Scotophilus altilis Allen, 1914 (Chiroptera: Vespertilionidae) - Vallo, Peter; Reeder, Deeann M.; Vodzak, Megan E.; Benda, Petr (Zootaxa, 2019)
Several house bat specimens superficially resembling the white-bellied house bat Scotophilus leucogaster (Cretzschmar, 1830), were recently captured in southwestern Ethiopia and southern South Sudan. These S. cf. leucogaster differed from typical S. leucogaster by their slightly smaller size and ventral coloration, conforming instead with the original description of S. altilis Allen, 1914. Scotophilus altilis is an overlooked taxon known from the Blue Nile region in Sudan that is currently considered a junior synonym of S. leucogaster. Phylogenetic analysis of mitochondrial cytochrome b gene (cytb) sequences revealed S. cf. leucogaster as a sister clade to S. leucogaster with a genetic distance of ca. 10%. Comparative specimens of questionable S. nigritellus de Winton, 1899 from northwestern Ethiopia and a wing biopsy sample of another S. cf. leucogaster from western Kenya also fell within this clade. Sequence data from two nuclear markers (zfy and fgb7) corroborated the distinction of S. cf. leucogaster from S. leucogaster. Likewise, morphometric analysis of cranial data largely supported this distinction, as well as taxonomic affiliation with S. altilis based on comparison with the only available paratype specimen. The position of this paratype specimen within the new Scotophilus clade, inferred from analysis of a short fragment of cytb, confirmed its taxonomic identity. Based on the presented evidence, the overlooked East African taxon S. altilis should be resurrected as a full species within the genus Scotophilus.